(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Micro businesses are critical to the development of the nation. According to the sector estimated by The World Bank, this sector accounts for about 31 million workers, estimated among 12.8 million enterprises and Micro enterprises are approximately four times more intensive in the use of human resources. Natural resources and human resources are both important in determining a country’s economy. When other developing nations across the world made it a priority to foster the development of women’s small-business ventures, they turned their attention to India. A large number of women-owned businesses have a substantial impact on their economy. In this study, we have discussed the women entrepreneurs and concept of women entrepreneurs and the existing pattern of micro-enterprises taken up by them in which firstly we have given the general overview of the topic then we done our study using the sample study area of Kanpur district with 80 women entrepreneur as a respondent sample.